Reverse pharmacology of phytoconstituents of food and plant in the management of diabetes: Current status and perspectives. (April 2021) - Sudhakar, Kalvatala; Mishra, Vijay; Hemani, Varshik; Verma, Arpit; Jain, Ankush; Jain, Sanjay; Charyulu, R. Narayana
Abstract: Background: The history and the discovery of the benefits of traditional medicines are fascinating over wide variety of disease. Various molecules have been erupted from traditional medicine for various diseases through reverse pharmacology. In current scenario plant-based medicines backed by modern scientific evidences are one of the most promising therapies in diabetes management. Scope and approach: Garlic (allicin), European barberry (berberine), Bitter gourd (charantin, polypeptide-p), Sweet potato (adiponectin, tiliroside), Orka (quercetin, hyperin) are some plants that have been used in folk medicine as well as traditional healing systems and are being assessed for their hypoglycemic effects in modern medicine. Key findings and conclusions: "Old wine in new bottle" proverb applies traditional medicine in new modern medicine. Various novel delivery aspects have modified the pharmacokinetics of phytochemicals and indirectly enhance the bioavailability, which in turn gives fruitful effect of their therapeutic action. Graphical abstract: Image 1 Highlights: Involvement of reverse pharmacology in transformation of traditional medicine into modern science based medicine. Medicinal potential of phytoconstituents. Potential biological activities as antioxidant and antidiabetic activity. Studies on the antidiabetic effects of herbal extracts can have promising results. Berberine, a benzylisoquinoline alkaloid, is useful in diabetes management.